PENGEMBANGAN E-BOOKLET BERBASIS WORDWALL MATERI PERUBAHAN WUJUD BENDA UNTUK MENINGKATKAN SELF-CONFIDENCE KELAS IV SDN KALITENGAH 1 - Dwi Kurniasari; Cindya Alfi; Mohammad Fatih (Cerdas Proklamator, 2024)
Put your abstract here. Use single spacing and don’t exceed 250 words. Put your abstract here. Use single spacing and don’t exceed 250 words. Consisting of introductory sentences, objectives, methods, results, and conclusions (Times New Roman 12) This research aims to develop digital learning tools in the form of wordwall-based e-booklets to increase students' self-confidence. This research uses the ASSURE development model which consists of the following main stages: Analyze learner characteristics, State objectives, Select methods, media, and materials, Utilize materials, Require learner participation, and Evaluation and revision. The tool used for evaluation is a questionnaire. Product validation tests involve media, material and language experts. The validity test carried out by these experts showed very valid results, with a score of 95% by media experts, 95% by material experts, and 92.5% by language experts. The feasibility test carried out by the class teacher resulted in a 100% assessment in the very feasible category. Apart from that, this research shows a significant increase in self-confidence, as evidenced by the N-Gain value of 0.87 which shows a high level of increase.